Experimenting with innovation processes: the case of reinventing a museum through collaboration - Marine Agogué; Anna Yström (CERN IdeaSquare Journal of Experimental Innovation, 2017)
This paper explores how experimenting with collaborative processes contributes to reinventing the purpose and practices of an organisation. Based on a case study of the Insectarium of Montréal, we focus on the 2-year collaborative process orchestrated by the director, involving employees, experts and visitors. Our findings show several organisational implications of engaging in this type of experimentation: specifically, beyond enabling the collective generation of new ideas, experimenting through collaboration is an excellent opportunity to renew the organisation’s practices and support the development of a reflexive leadership. This suggests that despite the inherent challenges associated with organisational experiments, there are clear benefits of engaging in such experiments to stimulate innovation.